Serotype skewing and immune imprinting shape response to the tetravalent dengue virus Qdenga vaccine - Luciana Conde; Valter Monteiro; Joao C.R. Freitas; Jameson Crandell; Lauren Lawres; Fernanda Tana; Mallery I. Breban; Fahima Akther; Jordan Polster; Abigail Porzucek; Tauyne M. Ramiro; Ana B. de Oliveira; et al. (Journal of Experimental Medicine, 2026)
Dengue causes over 390 million annual infections globally. Qdenga (TAK-003), the only widely available dengue vaccine, has an incompletely defined immunological profile. We performed longitudinal immunological profiling of 110 adults from a dengue-endemic region, including older adults (≥65 years), to assess the effects of immune imprinting and vaccine design on humoral and cellular immunity. Qdenga elicited B and T cell activation across groups but generated serostatus-dependent, serotype-skewed antibody responses. Only 8% of DENV-naïve individuals developed tetravalent neutralizing responses, whereas one-third responded to a single serotype, predominantly DENV-2, the vaccine backbone. DENV-exposed individuals mounted broader responses shaped by preexisting immunity, yet DENV-4 neutralization remained consistently poor. Neutralizing antibody titers plateaued after the first dose, with no increase following the second. These findings clarify why balanced tetravalent immunity is rarely achieved with Qdenga and demonstrate that both immune imprinting and vaccine backbone limit the breadth and magnitude of the responses. This has important implications for deployment, long-term protection in naive populations, and DENV-4–targeted boosters.